Genome-Wide Association Mapping of Hulless Barely Phenotypes in Drought Environment - Li, Jie; Yao, Xiaohua; Yao, Youhua; An, Likun; Feng, Zongyun; Wu, Kunlun (Frontiers in Plant Science, 2022)
Drought stress is one of the main factors restricting hulless barley (Hordeum vulgare L. var. nudum Hook. f.) yield. Genome-wide association study (GWAS) was performed using 269 lines of hulless barley to identify single-nucleotide polymorphism (SNP) markers associated with drought resistance traits. The plants were cultured under either normal or drought conditions, and various quantitative traits including shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, leaf fresh weight, leaf saturated fresh weight, leaf dry weight, ratio of root and shoot fresh weight, ratio of root and shoot dry weight, shoot water loss rate, root water loss rate, leaf water content and leaf relative water content, and field phenotypes including main spike length, grain number per plant, grain weight per plant, thousand grain weight, main spike number, plant height and effective spike number of plants were collected. After genotyping the plants, a total of 8,936,130 highly consistent population SNP markers were obtained with integrity > 0.5 and MAF > 0.05. Eight candidate genes potentially contributed to the hulless barley drought resistance were obtained at loci near significant SNPs. e.g. EMB506, DCR and APD2 genes for effective spike number of plants (ESNP), ABCG11 gene for main spike number (MEN), CLPR2 gene for main spike length (MSL), YIP4B gene for root and shoot dry weight (RSWD), and GLYK and BTS genes for thousand grain weight (TGW). The SNPs and candidate genes identified in this study will be useful in hulless barley breeding under drought resistance.